The pedagogical significance of the stages and methods of teaching volleyball - Fatullaeva Muazzam Azimovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
The article describes the stages, methods and means of teaching volleyball lessons through techniques in order to achieve high efficiency